2022
DOI: 10.1101/2022.07.22.22277720
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Communication under sharply degraded auditory input and the “2-sentence” problem

Abstract: Introduction: Many cochlear implant (CI) users who do quite well in standard clinical tests of speech perception report that a great amount of effort is required when listening in real-world situations. We hypothesize that the combined constraints of the sharply degraded signal provided by a CI and finite cognitive resources may lead to a "tipping point" when listeners are confronted with speech material that is more complex than the single words or single sentences that are used in clinical tests. Beyond this… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…Notably, this result emerged only for those CI listeners whose speech recognition score was minimally affected by the presence of the second sentence in the series; CI listeners who showed a two-sentence decrement failed to show this effort allocation pattern. Gathering observations bySvirsky et al (2024),Winn and Moore (2018) and the current study, it appears that listeners who excel at speech recognition (either younger TH listeners or better-performing CI listeners) show temporal allocation of listening effort that reflects the demands of the task and in-the-moment anticipation. Absence of this effect might be explained by a phenomenon observed byZekveld et al (2019) who found that the reliable effects of SNR/sentence intelligibility for pupil responses was entirely overridden by the presence of an extra memory load task during the experiment.Supporting the notion that effort allocation reflects strategic use of cognitive resources, recent results byJohns et al (2024) suggest that listening effort depends at least partly on the extent to which individuals have mobilized their attention in anticipation of the difficulty of the upcoming task Vaden et al (2022).…”
supporting
confidence: 56%
See 2 more Smart Citations
“…Notably, this result emerged only for those CI listeners whose speech recognition score was minimally affected by the presence of the second sentence in the series; CI listeners who showed a two-sentence decrement failed to show this effort allocation pattern. Gathering observations bySvirsky et al (2024),Winn and Moore (2018) and the current study, it appears that listeners who excel at speech recognition (either younger TH listeners or better-performing CI listeners) show temporal allocation of listening effort that reflects the demands of the task and in-the-moment anticipation. Absence of this effect might be explained by a phenomenon observed byZekveld et al (2019) who found that the reliable effects of SNR/sentence intelligibility for pupil responses was entirely overridden by the presence of an extra memory load task during the experiment.Supporting the notion that effort allocation reflects strategic use of cognitive resources, recent results byJohns et al (2024) suggest that listening effort depends at least partly on the extent to which individuals have mobilized their attention in anticipation of the difficulty of the upcoming task Vaden et al (2022).…”
supporting
confidence: 56%
“…Variation in the conditional front-loading or pacing of effort was also observed by Svirsky et al (2024). In their experiment, the pupil response during the presentation of a sentence grew at a slower rate when listeners were cued to anticipate two sequential sentences.…”
Section: Effort Anticipation and The Allocation Of Effort Across Timementioning
confidence: 78%
See 1 more Smart Citation